Novel Roles of the Master Transcription Factors Spo0A and σ(B) for Survival and Sporulation of Bacillus subtilis at Low Growth Temperature - Méndez, Marcelo B. (American Society for Microbiology, 2004)
Spore development and stress resistance in Bacillus subtilis are governed by the master transcription factors Spo0A and σ(B), respectively. Here we show that the coding genes for both regulatory proteins are dramatically induced, during logarithmic growth, after a temperature downshift from 37 to 20°C. The loss of σ(B) reduces the stationary-phase viability of cold-adapted cells 10- to 50-fold. Furthermore, we show that σ(B) activity is required at a late stage of development for efficient sporulation at a low temperature. On the other hand, Spo0A loss dramatically reduces the stationary-phase viability of cold-adapted cells 10,000-fold. We show that the requirement of Spo0A for cellular survival during the cold is independent of the activity of the key transition state regulator AbrB and of the simple loss of sporulation ability. Furthermore, Spo0A, and not proficiency in sporulation, is required for the development of complete stress resistance of cold-adapted cells to heat shock (54°C, 1 h), since a loss of Spo0A, but not a loss of the essential sporulation transcription factor σ(F), reduced the cellular survival in response to heat by more than 1,000-fold. The overall results argue for new and important roles for Spo0A in the development of full stress resistance by nonsporulating cells and for σ(B) in sporulation proficiency at a low temperature.